2017
DOI: 10.1057/s41300-017-0029-0
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual harassment of students on public transport: an exploratory study in Lucknow, India

Abstract: Studies suggest that incidents of sexual harassment are common occurrence on public transport in India, but there is little reliable data to understand and tackle the problem. This research explores actual and witnessed victimisations as well as perceptions of the risk by a sample of 200 tertiary female students in Lucknow, India. Consistent with literature, sexual harassment victimisation appears to be most prevalent in buses and increases with the frequency of use of public transport. We found that the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…In this regard, women who were sexually harassed often ruminate about their past experiences which causes them to reflect on negative thoughts, self-harm, and low self-esteem, which amplifies loneliness, hopelessness, and helplessness, and develops symptoms of depression 8,9. In addition, victims, while using public transportation, tend to have a fear of getting sexually harassed, and this has caused women to modify their travel routes or restrict their use of public transport at all 10,11. This leads to the reduction of their capability to participate in professional as well as educational activities and also in public life 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, women who were sexually harassed often ruminate about their past experiences which causes them to reflect on negative thoughts, self-harm, and low self-esteem, which amplifies loneliness, hopelessness, and helplessness, and develops symptoms of depression 8,9. In addition, victims, while using public transportation, tend to have a fear of getting sexually harassed, and this has caused women to modify their travel routes or restrict their use of public transport at all 10,11. This leads to the reduction of their capability to participate in professional as well as educational activities and also in public life 12.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the use of public transport has become common among women mainly for the purpose of education and work 13. But research has also shown that concerns about safety have negatively affected the travel decisions of women 10…”
Section: Introductionmentioning
confidence: 99%
“…Eve teasing (street harassment) and sexual harassment have far-reaching consequences, including both short and long-term socio-emotional consequences and limited access to education for victims (Talboys et al, 2017). Participants' stories highlighted harassment experienced on public transportation, which other studies have found to be commonplace (Dhillon & Bakaya, 2014;Gekoski, Gray, Adler, & Horvath, 2017;Leach & Sitaram, 2007;Tripathi, Borrion, & Belur, 2017). Given the widespread familial and social prohibitions limiting young women's movement, harassment in public and on public transportation remains a significant barrier to young women's education and employment opportunities, as is seen elsewhere in developing countries (Porter et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(c.f. Mazumder and Pokharel 2019;Gekoski et al 2017;Ceccato and Paz 2017;Natarajan et al 2017;Tripathi et al 2017;Chui and Ong 2008). A number of studies have also located the solutions to VAW on public transport in situational measures (c.f.…”
Section: Situational Factors That Facilitate Crimementioning
confidence: 99%